2008
DOI: 10.1097/mlr.0b013e31815b979a
|View full text |Cite
|
Sign up to set email alerts
|

Twelve Month Use of Mental Health Services in a Nationally Representative, Active Military Sample

Abstract: Despite recent efforts to de-stigmatize mental health problems and treatments, unmet need for mental health services remains a significant problem in active militaries. Our findings indicate that military institutions should continue public education campaigns to de-stigmatize mental health problems and should make necessary changes in health delivery systems to gain the trust of military members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 19 publications
4
89
2
Order By: Relevance
“…Other programs that incorporate peer support (23)(24)(25) or family support (26) show promise to provide effective and favorable options for returning soldiers. Barriers to care affect soldiers' decisions to seek help (13,20). In this study, soldiers who used any source of help reported the three types of barriers-stigma, negative attitudes, and organizational barriers-to be lower than did soldiers who did not use help from any source.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Other programs that incorporate peer support (23)(24)(25) or family support (26) show promise to provide effective and favorable options for returning soldiers. Barriers to care affect soldiers' decisions to seek help (13,20). In this study, soldiers who used any source of help reported the three types of barriers-stigma, negative attitudes, and organizational barriers-to be lower than did soldiers who did not use help from any source.…”
Section: Discussionmentioning
confidence: 81%
“…Research has indicated that symptom severity is associated with use of mental health help (20). To account for this effect, additional analyses were conducted that added depression, anxiety, and PTSD symptom severity to each of the four models (results not shown).…”
Section: Effects Of Barriers To Care On Source Of Help Usedmentioning
confidence: 99%
“…Further challenges may occur if the mental health problems go untreated when the military personnel complete their military service. If veteran couples never discuss their concerns with their medical provider or they were not properly assessed in a healthcare setting, initial mental health symptoms can go untreated and worsen over time for both partners (Fikretoglu et al 2008). Including a specialist who is trained to briefly assess for mental health symptomology and collaborate with medical professionals into the treatment plan and protocol of military health visits may reduce the number of untreated personnel and veterans (and their partners).…”
Section: Integrated Care With Military and Veteran Couplesmentioning
confidence: 95%
“…Evidence from both military 4 and civilian 5 settings has shown that problems with the recognition of need represents by far the most prevalent barrier to receiving care. Fikretoglu et al 4 and Wang 5 have shown that 80-96% of those who might benefit from care do not seek care having failed to recognize their own treatment needs; such individuals acknowledge clear-cut symptoms of mental disorders but deny any need for care. Individuals with mental health problems who do recognize a need for care often face a number of potential barriers to care, including problems with availability, accessibility and acceptability.…”
Section: Introductionmentioning
confidence: 99%